(untitled) - Tindall, George Brown (New York, 2004)
Full of vivid characters and events, this survey explores American history from pre-Columbian civilizations through to the era of Civil War reconstruction. It introduces American history at a level suitable for college students.
Keywords: United States,Hoa Kỳ; History,Lịch sử